Effect of active vitamin D3 on VEGF-induced ADAM33 expression and proliferation in human airway smooth muscle cells: implications for asthma treatment. Issue 1 (December 2017) - Kim, Sung-Ho; Pei, Qing-Mei; Jiang, Ping; Yang, Min; Qian, Xue-Jiao; Liu, Jiang-Bo
Abstract Background Asthma is a chronic respiratory disease characterized by reversible airway obstruction with persistent airway inflammation and airway remodeling, which is associated with increased airway smooth muscle (ASM) mass. Vascular endothelial growth factor (VEGF) has been implicated in inflammatory and airway blood vessel remodeling in asthma. Recent evidence indicates that a deficiency of 1, 25-dihydroxyvitamin D3 (1, 25(OH)2D3) may influence asthma pathogenesis. A disintegrin and metalloproteinase (ADAM)33 has been identified as playing a role in the pathophysiology of asthma. ADAM33, which is expressed in ASM cells, is suggested to play a role in the function of these cells. Recent studies show that 1, 25-(OH)2D3 exerts direct inhibitory effects on passively sensitized human ASM cells in vitro, including inhibition of ADAM33 expression and cell proliferation; however, the mechanism has not been fully understood. Methods In order to elucidate the precise mechanism underlying the effect of 1, 25(OH)2D3 on VEGF-induced ADAM33 expression and ASM cell proliferation, we tested the effects of 1, 25(OH)2D3 on cell cycle progression and evaluated the levels of phospho-VEGF receptor 2 (VEGFR2), phospho-extracellular signal-regulated kinase 1/2 (ERK1/2), and phospho-Akt in VEGF-stimulated ASM cells. Results We found that 1, 25(OH)2D3 inhibited VEGF-induced ADAM33 expression and ASM cell proliferation, as well as cell cycle arrest. Additionally, VEGF-induced ADAM33 expression and ASM cell proliferation was suppressedvia inhibition of ERK1/2 activity, but not that of Akt. Furthermore, 1, 25(OH)2D3 treatment inhibited VEGF-induced activation of VEGFR2 as well as that of ERK and Akt in a concentration-dependent manner. 1, 25(OH)2D3 also inhibited transforming growth factor (TGF)-β-induced VEGF secretion by ASM cells. Conclusions Collectively, our findings suggest that 1, 25(OH)2D3 inhibits VEGF-induced ASM cell proliferation by suppressing VEGFR2 and ERK1/2 activation and downregulating ADAM33. Further studies of these mechanisms are needed to facilitate the development of treatments for smooth muscle hyperplasia-associated diseases of the airway such as asthma.